Gamification and interactive learning: a strategy for reducing mathematics’ anxiety / Fuziatul Norsyiha ... [et al.] - Norsyiha, Fuziatul; Omar, Mawardi; Samsudin, Norshuhada; Wan Mohd Rosly, Wan Nur Shaziayani (Unit Penerbitan JSKM, 2024)
Innovations like gamification and interactive learning have revolutionized digital education by altering the way standard online teaching approaches are used. This is due to the fact that gamification in e-learning is redefining conventional educational methods and offering a creative way to increase student motivation, engagement, and retention of the material. Mathematics is often perceived as one of the most challenging subjects, with many students experiencing anxiety with a feeling of tension, fear, or apprehension that interferes with mathematical performance. This anxiety can lead to avoidance of math-related tasks, lower confidence, and poor academic outcomes. With the rise of online education, new teaching strategies are needed to create engaging and stress-free learning environments. One promising approach is gamification and interactive learning, which integrate game-based elements such as points, badges, challenges, and adaptive feedback to make learning mathematics more enjoyable and less intimidating. By shifting the focus from memorization to an interactive, problem-solving experience, gamification can help students develop a positive mindset toward mathematics while improving motivation and retention. This paper explores the types and roles of gamification in reducing mathematics anxiety and the impact on student engagement and confidence in learning mathematics.